Gambaran Karakteristik Pasien HIV/AIDS yang Mendapat Terapi Antiretroviral (ARV) di Puskesmas Kota Samarinda pada Tahun 2020-2023 - Frisky Kandenapa, Gabriel; Iskandar, Abdillah; Kartini, Agnes (ITKES Wiyata Husada Samarinda, 2026)
HIV/AIDS remains a global health issue, particularly in regions with high-risk key populations. Samarinda City is noted as one of the areas with a significant burden of HIV/AIDS cases in East Kalimantan. This study aims to describe the characteristics of HIV/AIDS patients receiving antiretroviral therapy (ART) at five primary health centers (Puskesmas) in Samarinda from 2020 to 2023. This descriptive retrospective study included a total sample of 493 patients whose data were obtained from computer-based medical records. The variables analyzed included age, gender, domicile, education, marital status, transmission risk factors, types of ART regimen, and ART side effects.Most patients were aged 20–29 years (50.9%), male (77.9%) and (77.5%) reported male-to-male sexual contact (MSM) as the primary transmission risk factor. A total of (89.9%) resided in Samarinda, the most commonly used ART regimen was TDF + FTC + EFV (97.6%) and the majority of patients (99.4%) experienced no side effects. However, data on education and marital status were largely incomplete. HIV/AIDS patients receiving ART in Samarinda were predominantly young males, with MSM identified as the primary risk group.